Avatar, Identitas dalam Cyberspace - Damayanti, Maria Nala; Yuwono, Elisabeth Christine (Nirmana, 2013)
Human dependence on technology will have implications for a new culture of communication. Culture is related to the person behind the presence of elements of verbal or visual communication through internet media. Communication established via the Internet, known as cyberspace, allows the presence of a person in a variety of virtual identities. These identities emerge through verbal and visual appearances. They have names and shapes but can be present in any kind of form, commonly called avatars. The identity of a person can be represented by a number of different avatars capable of having more than one party at the same time. Communication that exists in cyberspace exceed time and space. The presence of these identities clearly indicates a relationship model that has a specific purpose. It could be a model of social relations that promote friendship, excitement, a sense of play, a critical mind or with other purposes. But the presence of such virtual identity cannot simply be equated with human beings as their personal identity in the real world, because in cyberspace, identity is plural and fluid. It can even be made with a hidden agenda.